Improvement of surgical performance of medical students after basic surgical suturing workshops - Maria Golebiowska; Beata Golebiowska; Ting-I Huang; Tzu Chi Kuo (Kazimierz Wielki University, 2018)
Introduction Surgery, subject considered as one of the most demanding in medical education, fascinates medical students for centuries. And despite the possibilities of surgical observerships, as well as the passion and dreams of young adepts of medicine to acquire practical skills and experience in this fascinating field, we observe lack of practical aspect in medical undergraduate training. In order to allow medical students to experience basics of surgical reality, every year our team performs surgical suturing workshops for more than 50 students from all years within non-formal peer-to-peer education model. The Aim of the Study The aim of this study is to present the effectiveness of basic suturing training among 145 international students of Medical University of Lublin. Materials and methods The study group included 145 international students with no prior or little practical surgical experience, who attended surgical workshops in 15-participant groups in years 2014-2016. Both knowledge and technical performance were rated before and after conduction of the workshops. Results Within theoretical part of the training, 84% increase of knowledge in surgical procedures was observed. As for the practical skills, 71% of attendees decreased time of basic and continuous sutures performance by at least 50%. Non-formal peer-to-peer education model, as well as small groups and sufficient time for practice were noted as essential factor to the significant results of conducted workshop. Conclusions Basic surgical skills workshops serve as a great example of non-formal peer-to-peer training which improves practical abilities among attendees, as well as didactic and teamwork skills among senior students.